2016
DOI: 10.1038/ng.3606
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy within the mammary STAT5-driven Wap super-enhancer

Abstract: Super-enhancers comprise of dense transcription factor platforms highly enriched for active chromatin marks. A paucity of functional data led us to investigate their role in the mammary gland, an organ characterized by exceptional gene regulatory dynamics during pregnancy. ChIP-Seq for the master regulator STAT5, the glucocorticoid receptor, H3K27ac and MED1, identified 440 mammary-specific super-enhancers, half of which were associated with genes activated during pregnancy. We interrogated the Wap super-enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
299
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(335 citation statements)
references
References 83 publications
20
299
7
Order By: Relevance
“…Moreover, the high levels of STAT5 drive the formation of additional mammaryspecific enhancers and superenhancers (62). Notably, mutation of a STAT5 consensus element within a constituent enhancer of the STAT5-driven mammary Wap superenhancer by genome editing technologies prevents enhancer formation (62). Likewise, HMGN2 and H1 have also been implicated in enhancer function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the high levels of STAT5 drive the formation of additional mammaryspecific enhancers and superenhancers (62). Notably, mutation of a STAT5 consensus element within a constituent enhancer of the STAT5-driven mammary Wap superenhancer by genome editing technologies prevents enhancer formation (62). Likewise, HMGN2 and H1 have also been implicated in enhancer function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, STAT5 has been shown to bind to a mammary-specific autoregulatory enhancer in the intergenic region between Stat5a and Stat5b, and this feed-forward loop contributes to the high levels of STAT5 in mammary tissue (61). Moreover, the high levels of STAT5 drive the formation of additional mammaryspecific enhancers and superenhancers (62). Notably, mutation of a STAT5 consensus element within a constituent enhancer of the STAT5-driven mammary Wap superenhancer by genome editing technologies prevents enhancer formation (62).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is very likely that many such clusters will not act as a single unit (Hay et al 2016;Shin et al 2016), and we find many of them carrying both "with" and "without" peaks (Supplemental Fig. S6).…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…Interestingly, we did not find a case where removal of one enhancer eliminated expression of the target gene. Similarly, individual deletion of three constituent enhancers of the Wap super-enhancer revealed their partially redundant role in regulating transcription of Wap (Shin et al 2016). Furthermore, Hay et al (2016) showed by deletions within the Hba super-enhancer that each constituent enhancer acts independently in an additive manner to regulate expression of Hba genes in vivo.…”
Section: Enhancer and Super-enhancer Equivalencementioning
confidence: 99%
“…The SCR overlaps a predicted super-enhancer and was found to be required for >85% of the transcript levels of Sox2 in ES cells. Similarly, other studies have revealed the role of select super-enhancers in gene regulation (Mansour et al 2014;Hnisz et al 2015;Hay et al 2016;Huang et al 2016;Shin et al 2016). At the Sox2 locus, an additional super-enhancer was predicted surrounding the Sox2 gene; however, deletion of the enhancers within that region revealed that they are not required for Sox2 transcription in ES cells, thus raising questions about the super-enhancer prediction model (Zhou et al 2014).…”
mentioning
confidence: 94%